2007
DOI: 10.1002/bmc.887
|View full text |Cite
|
Sign up to set email alerts
|

Development of a two‐step chromatography procedure that allows the purification of a high‐purity anti‐histone H1 monoclonal immunoglobulin M antibody with immunosuppressant activity

Abstract: Abbreviations used: ELISA, enzyme-linked immunosorbent assay; FCA, Freund's complete adjuvant; FCS, fetal calf serum; IgG, immunoglobulin G; IgM, immunoglobulin M; mAb, monoclonal antibody; MHCH, major histocompatibility complex haplotype; MLR, mixed lymphocyte reaction; PBS, phosphate-buffered saline. ABSTRACT: In organ transplantation, the development of a novel immunosuppressant free of the need for permanent administration and any serious side effects has eagerly been awaited. We have previously reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Although this study has revealed novel mechanisms for immune modulation, much work remains for understanding the immunological aspects of anti‐histone H1 autoantibody in inflamed liver and liver allograft tolerance. Specifically, future work will focus on the in vitro and in vivo function of anti‐histone H1 mAb, which possesses mixed lymphocyte reaction–inhibitory activity 40 and on the characterization of cell‐surface histone H1(‐like) antigens that are transiently expressed during T‐cell activation 7 and also DC maturation 19 …”
Section: Discussionmentioning
confidence: 99%
“…Although this study has revealed novel mechanisms for immune modulation, much work remains for understanding the immunological aspects of anti‐histone H1 autoantibody in inflamed liver and liver allograft tolerance. Specifically, future work will focus on the in vitro and in vivo function of anti‐histone H1 mAb, which possesses mixed lymphocyte reaction–inhibitory activity 40 and on the characterization of cell‐surface histone H1(‐like) antigens that are transiently expressed during T‐cell activation 7 and also DC maturation 19 …”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed the great potential of histone H1 vaccination in transplant recipients for tolerance induction [80, 81]. To further explore the roles of histone H1 and its future clinical application, we have generated antihistone H1 monoclonal antibodies (clone: 16G9, IgM), which possess immunosuppressive activity in vitro [82]. In addition, we have identified the functional epitope (SSVLYGGPPSAA) responsible for the immunosuppressive activity of 16G9 and have confirmed the diagnostic and therapeutic potential of histone H1 peptide [83].…”
Section: Nuclear Antigens As a Therapeutic Targetmentioning
confidence: 70%
“…16G9 mAb was generated as a tool to elucidate the mechanism of immunological tolerance in liver transplantation (19) and was found to have MLR-inhibitory activity (data not shown). Here, we used phage display to identify peptides from a large library that bind to Ab-binding sites, thereby mimicking the conformational features of both linear and conformational epitopes.…”
Section: Discussionmentioning
confidence: 99%